Serum C-reactive Protein Predicts Early Mortality in Patients with Decompensated Cirrhosis of Liver - Islam, Md Atikul; Alam, Sheikh Mohammad Noor E; Das, Dulal Chandra; Khaleque, Narwana; Yousuf, M Abul Khair; Mahtab, Mamun Al (Bangladesh Medical Journal, 2021)
Serum C-reactive protein is a marker of systemic inflammation, which has been studied to predict mortality and cirrhosis related complication in decompensated cirrhosis of liver. To evaluate the role of serum C- reactive protein as a predictor of early mortality in patients with decompensated cirrhosis of liver. This was a prospective observational study, carried out in the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University, Dhaka between October 2017 to February 2019. A total of 89 patients with decompensated cirrhosis of liver were included in the study. Baseline serum CRP was measured and patients were longitudinally followed for a period of 30 days. Patients were divided into two groups, survival and non-survival. The groups were compared of CRP level, CTP score, MELD score and cirrhosis related complications. Chi-Square test was used to analyze the categorical variables and Student t-test was used to analyze continuous variables. Receiver-operator characteristic curve was used to detect serum CRP level for prediction of mortality within 30 days. The mean age was found 49.02±13.90 years in survival group and 47.52±11.30 years in non-survival group. Male patients were predominant in both groups. Total WBC count, serum CRP, serum sodium, serum bilirubin, CTP score & MELD score were statistically significant (p<0.05) between the groups. In multivariate analysis, only serum CRP level (OR 1.075, 95% CI, 1.027-1.122%, p=0.001) was found significantly associated with mortality within 30 days. Receiver-operator characteristic (ROC) was constructed, using serum CRP level, which gave a cut off value of 31mg/L, with 78% sensitivity and 90% specificity for prediction of mortality within 30 days. Elevated serum CRP level is an independent predictor of early mortality in patients with decompensated cirrhosis of liver. It was also observed that, high serum CRP level was associated with increased frequency of cirrhosis related complications. Bangladesh Med J. 2020 Jan; 49 (1): 1-6